Negative pole piece, battery monomer, battery and electric device

By using silicon-based materials and specific functional group adhesives in the negative electrode film layer of lithium-ion batteries, the problems of volume expansion and mold release during battery circulation are solved, and the circulation performance and stability of the battery are improved.

CN119230716APending Publication Date: 2024-12-31CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202310796969.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

During the circulation process, lithium-ion batteries have serious problems such as volume expansion, mold release and powder loss, resulting in poor circulation performance.

Method used

The silicon-based material and a binder containing hydroxyl, carboxyl, amino, cyano, lipo, and vinyl functional groups were added to the negative electrode film layer. The volume average particle size of the binder was 0.1 μm-0.8 μm, and the crosslinking degree was 50-100, the swelling rate is 5%-80%, the glass transition temperature is -20℃-60℃, and the elongation is 50%-400%, so as to improve the bonding and cohesion of the negative electrode sheet and inhibit volume expansion and demolding.

Benefits of technology

It effectively improves the cycling performance of the battery, reduces the demolding and powder loss of the negative electrode sheet, and improves the stability and energy density of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230716A_ABST
    Figure CN119230716A_ABST
Patent Text Reader

Abstract

The embodiment of the invention provides a negative pole piece, a battery monomer, a battery and an electric device. The negative electrode plate comprises a negative electrode current collector and a negative electrode film layer arranged on at least one side of the negative electrode current collector; the negative electrode film layer comprises a negative electrode active material and a binder, and the negative electrode active material comprises a silicon-based material; wherein the binder comprises at least one of the following functional groups: hydroxyl, carboxyl, amino, cyano, lipid group and vinyl. According to the technical scheme provided by the invention, the cohesive force and cohesive force of the negative pole piece can be improved, so that powder falling and demolding of the pole piece in the production process are reduced, and the cycle performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and more specifically, to a negative electrode plate, a battery cell, a battery and an electrical device. Background Art

[0002] In recent years, lithium-ion batteries have been used in more and more fields, such as wind power, hydropower, thermal power generation, solar power stations and other energy storage power supply fields, as well as electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. While lithium-ion batteries have made great progress, higher requirements have been put forward for their performance in all aspects.

[0003] Therefore, how to improve the cycle performance of lithium-ion batteries is an urgent problem to be solved. Summary of the invention

[0004] The present application is made in view of the above-mentioned problems, and its purpose is to provide a negative electrode plate, a battery cell, a battery and an electrical device to improve the cycle performance of the battery.

[0005] In a first aspect, a negative electrode plate is provided, comprising a negative electrode current collector and a negative electrode film layer arranged on at least one side of the negative electrode current collector; the negative electrode film layer comprises a negative electrode active material and a binder, and the negative electrode active material comprises a silicon-based material; wherein the binder comprises at least one of the following functional groups: hydroxyl, carboxyl, amino, cyano, lipid, and vinyl.

[0006] In the embodiment of the present application, the negative electrode plate includes a negative electrode film layer; and the negative electrode film layer includes a negative electrode active material and a binder, and the negative electrode active material includes a silicon-based material. The binder includes at least one functional group selected from the group consisting of hydroxyl, carboxyl, amino, cyano, lipid, and vinyl. By adding silicon-based materials and binders to the negative electrode film layer, on the one hand, the theoretical specific capacity of the silicon-based material is higher, which is beneficial to improving the energy density of the battery; on the other hand, the silicon-based material is harder and not easily crushed when cold pressed, and the particle shape is relatively irregular, with certain gaps between particles. Therefore, the negative electrode sheets containing silicon-based materials generally have a larger porosity, and the binders containing at least one functional group of hydroxyl, carboxyl, amino, cyano, lipid, and vinyl have better adhesion. Adding a binder with better adhesion to the negative electrode film layer so that the binder is filled in the large pores of the silicon-based material can improve the cohesion of the negative electrode sheet and the adhesion between the negative electrode film layer and the negative electrode collector, so as to inhibit the serious volume expansion of the silicon-based material during the battery cycle and reduce the demolding and powder loss of the negative electrode sheet, thereby improving the cycle performance of the battery.

[0007] In a possible implementation, the volume average particle size Dv50 of the binder is 0.1 μm-0.8 μm; optionally, the volume particle size distribution Dv50 of the binder is 0.3 μm-0.7 μm; optionally, the volume average particle size Dv50 of the binder is 0.35 μm-0.45 μm.

[0008] In the embodiment of the present application, in order to improve the bonding and cohesion of the negative electrode sheet and improve the demoulding and powdering of the sheet, a binder containing at least one functional group of hydroxyl, carboxyl, amino, cyano, lipid, and vinyl is added to the negative electrode film layer to fill in the larger gaps of the silicon-based material. In addition, by making the volume average particle size Dv50 of the binder 0.1μm-0.8μm, further, 0.3μm-0.7μm, and further, 0.35μm-0.45μm, the binder with a moderate particle size is filled in the larger gaps of the silicon-based material, which can enhance the cohesion between the negative electrode active materials and the bonding between the negative electrode active materials and the negative electrode current collector, thereby further reducing the demoulding and powdering of the sheet, and improving the cycle stability of the battery.

[0009] In a possible implementation, the volume average particle size Dv50 of the binder is 0.5 μm-0.7 μm.

[0010] In the embodiment of the present application, in order to improve the bonding force of the negative electrode sheet and improve the demoulding and powdering of the sheet, a binder containing at least one functional group of hydroxyl, carboxyl, amino, cyano, lipid, and vinyl is added to the negative electrode film layer to fill in the larger gaps of the silicon-based material. Furthermore, by making the volume average particle size Dv50 of the binder 0.5μm-0.7μm, the bonding force in the negative electrode sheet can also be enhanced, the demoulding and powdering of the sheet can be reduced, and the cycle stability of the battery can be improved.

[0011] In a possible implementation manner, the degree of crosslinking of the binder is 50-100. Optionally, the degree of crosslinking of the binder is 80-98.

[0012] In the embodiment of the present application, if the degree of crosslinking of the binder is high, the amount of electrolyte absorbed by it will be less, and the slurry film formation of the negative electrode film layer will be slower, and the strength of the binder will be higher. Therefore, by keeping the degree of crosslinking of the binder at 50-100, especially 80-98, the strength of the binder and the electrolyte resistance performance can be improved. Maintaining the high strength of the binder is conducive to inhibiting the expansion of the negative electrode and improving the bonding force between the active materials in the negative electrode sheet, so as to reduce the probability of powder loss and demolding of the negative electrode sheet.

[0013] In a possible implementation manner, the swelling rate of the binder is 5%-80%. Optionally, the swelling rate of the binder is 10%-50%.

[0014] In the embodiments of the present application, the binder usually swells. If the swelling exceeds a certain degree, it will affect the conductivity and bonding force between the active material and the current collector, and further affect the battery capacity and cycle performance. Therefore, by limiting the swelling rate of the binder to 5%-80%, especially 10%-50%, the binder with a moderate swelling rate can achieve a better bonding effect, thereby further reducing the probability of powder loss and demolding of the negative electrode sheet.

[0015] In a possible implementation manner, the glass transition temperature of the binder is -20°C-60°C. Optionally, the glass transition temperature of the binder is -10°C-40°C.

[0016] In the embodiment of the present application, if the glass transition temperature is too high, it will affect the brittleness of the negative electrode sheet, and then cause the negative electrode sheet to release and fall off during the battery cycle. Therefore, by keeping the glass transition temperature of the binder at -20℃-60℃, especially -10℃-40℃, the brittleness of the negative electrode sheet can be further reduced.

[0017] In a possible implementation manner, the elongation of the adhesive is 50%-400%. Optionally, the elongation of the adhesive is 100%-200%.

[0018] In the embodiment of the present application, during the repeated expansion of the negative electrode sheet, the binder with a certain elongation can inhibit the expansion of the negative electrode sheet, thereby reducing the rupture or powdering of the sheet, etc. By making the elongation of the binder 50%-400%, especially 100%-200%, the binder can have a strong anti-deformation performance.

[0019] In a possible implementation, based on 100 parts by weight of the negative electrode film layer, the weight of the binder is 1 part by weight to 10 parts by weight. Optionally, the weight of the binder is 2 parts by weight to 8 parts by weight.

[0020] In the embodiment of the present application, in order to reduce the demoulding and powdering of the negative electrode sheet, a binder containing a specific functional group is added to the negative electrode film layer, so that the binder is filled in the larger pores in the negative electrode active material. By making the mass proportion of the binder in the negative electrode film layer 1%-10%, especially 4%-8%, it can not only improve the bonding force between the negative electrode active materials to inhibit the volume expansion of the negative electrode sheet, but also reduce the reduction in battery energy density caused by excessive binder content.

[0021] In a possible implementation, the binder includes at least one of styrene-butadiene and its modifications, styrene-acrylic and its modifications, polyurethane and its modifications, polyvinylidene fluoride and its modifications, and acrylate and its modifications.

[0022] In the embodiments of the present application, by using at least one of butadiene styrene and its modified products, styrene acrylic and its modified products, polyurethane and its modified products, polyvinylidene fluoride and its modified products, acrylate and its modified products with good bonding strength as a binder, it helps to further improve the bonding strength between the negative electrode active material and the negative electrode current collector.

[0023] In a possible implementation, the silicon-based material includes at least one of a silicon-oxygen material and a silicon-carbon material; optionally, the silicon-oxygen material includes SiO x , wherein 0.4≤x≤1.6; optionally, the silicon-carbon material includes a silicon-carbon composite, and based on the total mass of the silicon-carbon composite, the ratio of the mass content B of the carbon element to the mass content A of the silicon element in the silicon-carbon composite is 1.3≤B / A≤2.

[0024] In the embodiment of the present application, by adding silicon-based materials, especially silicon-oxygen materials or silicon-carbon materials, to the negative electrode active materials, it is beneficial to improve the energy density of the battery. The silicon-oxygen materials in the silicon-based materials not only have high theoretical capacity and excellent stability, but also have the advantages of low cost, non-toxicity and environmental friendliness; silicon-carbon materials have high theoretical capacity and good cycle performance. By using silicon-oxygen materials, especially SiO x , wherein 0.4≤x≤1.6, or using a silicon-carbon material in which the ratio of the mass proportion of silicon element to the silicon-carbon composite A to the mass proportion of carbon element to the silicon-carbon composite B is 1.3≤B / A≤2, can further improve battery performance.

[0025] In a possible implementation, the negative electrode active material further includes graphite; wherein, based on 100 parts by weight of the negative electrode film layer, the weight of the graphite is 45 parts by weight to 70 parts by weight, optionally, the weight of the graphite is 55 parts by weight to 65 parts by weight.

[0026] In the embodiment of the present application, the silicon-based material has a high theoretical capacity, but its conductivity is poor. Therefore, if only the silicon-based material is used as the negative electrode active material of the battery, the conductivity of the battery will be very poor. By adding graphite with good conductivity to the negative electrode active material and making the mass proportion of graphite in the negative electrode film layer 45%-70%, especially 55%-65%, the battery can maintain good cycle performance.

[0027] In one possible implementation, the compaction density of the negative electrode sheet is 1.0 g / cm 3 -2.5g / cm 3 Optionally, the compaction density of the negative electrode plate is 1.2 g / cm 3 -1.8g / cm 3 .

[0028] In the embodiment of the present application, by making the compaction density of the negative electrode sheet 1.0g / cm 3 -2.5g / cm 3 , especially 1.2g / cm 3 -1.8g / cm 3 , which can further improve the energy density of the battery.

[0029] In a possible implementation manner, the thickness of the negative electrode plate is 60 μm-150 μm. Optionally, the thickness of the negative electrode plate is 90 μm-130 μm.

[0030] In the embodiment of the present application, the energy density of the battery can be further improved by making the thickness of the negative electrode plate 60 μm-150 μm, especially 90 μm-130 μm.

[0031] The second aspect of the present application provides a battery cell, comprising the negative electrode plate described in any embodiment of the first aspect of the present application.

[0032] In a possible implementation, the battery cell further includes a positive electrode plate, the positive electrode plate includes a positive electrode collector and a positive electrode film layer provided on at least one side of the positive electrode collector, and the positive electrode film layer includes a positive electrode active material.

[0033] In one possible implementation, the positive electrode active material includes Li x (Ni a Co b Mn c ) 1-d M d O 2-y A y , wherein M includes at least one of Zr, Al, B, Ta, Mo, W, Nb, Sb, and La, 0.2<x≤1.2, 0.5≤a<1.0, 0≤b<0.5, 0≤c<1, 0≤d<1, and 0≤y<0.02.

[0034] A third aspect of the present application provides a battery, comprising the battery cell described in the second aspect of the present application.

[0035] The fourth aspect of the present application provides an electrical device, comprising the battery according to the third aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without paying creative work.

[0037] Figure 1 A schematic diagram of the structure of a negative electrode sheet according to an embodiment of the present application;

[0038] Figure 2 A schematic diagram of a battery cell according to an embodiment of the present application;

[0039] Figure 3 A schematic diagram of the structure of a battery cell according to an embodiment of the present application;

[0040] Figure 4 A schematic diagram of a battery according to an embodiment of the present application;

[0041] Figure 5 A schematic diagram of the structure of a battery according to one embodiment of the present application;

[0042] Figure 6 It is a schematic structural diagram of an electrical device according to one embodiment of the present application. DETAILED DESCRIPTION

[0043] The following describes the embodiments of the negative electrode sheet, battery cell, battery and electric device of the present application in detail with appropriate reference to the drawings, but unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of actually the same structure may be omitted. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0044] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a specific range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can form a scope with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0045] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0046] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0047] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, and can be performed sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), which means that step (c) can be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0048] If there is no special explanation, the "include" and "comprising" mentioned in this application represent open-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or comprised.

[0049] The terms "above", "below", "greater than" or "less than" as used in this application include the number, for example, "at least one" means one or more, and "at least one of A and B" means "A", "B" or "A and B".

[0050] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0051] Lithium-ion batteries are widely used in consumer electronics due to their high energy density, power and long cycle performance. In recent years, with the continuous development of electric vehicles and energy storage systems, people's requirements for battery cycle performance and other aspects are also increasing.

[0052] At present, the capacity of lithium-ion batteries using graphite materials as negative electrode active materials has gradually failed to meet the requirements of long-range electric vehicles. Silicon-based materials have become the most promising negative electrode materials for the next generation of lithium-ion batteries due to their large specific capacity, low discharge platform, and rich energy storage. However, silicon-based materials are severely limited in their commercial application due to their own factors. First of all, silicon-based materials have severe volume expansion during the battery cycle. The large volume change during the lithium insertion and extraction process can easily lead to particle pulverization and active materials falling off the current collector, which ultimately leads to powder loss, severe demolding, and poor cycle performance of the pole piece. Therefore, how to reduce powder loss and demolding of batteries using silicon-based materials so that they have better cycle performance is an urgent problem to be solved.

[0053] In view of this, the present application provides a negative electrode plate, which includes a negative electrode current collector and a negative electrode film layer arranged on at least one side of the negative electrode current collector. By adding a silicon-based material and a binder to the negative electrode active material in the negative electrode film layer, and making the binder include at least one of hydroxyl, carboxyl, amino, cyano, lipid, and vinyl, the binder with good bonding force is filled in the large pores of the silicon-based material, thereby suppressing the poor bonding force between the negative electrode active materials caused by the severe volume expansion of the silicon-based material during the battery cycle, thereby alleviating the powdering and demolding phenomena of the plate, and having good cycle performance.

[0054] The negative electrode sheet, battery cell, battery and electrical device of the present application are described below with reference to the accompanying drawings.

[0055] In addition, the technical solution of the present application is applicable to various types of batteries such as lithium-ion batteries, lithium metal batteries, sodium-ion batteries, etc., and the present application does not limit this; for the convenience of description, the following description will take lithium-ion batteries as an example.

[0056] [Negative electrode]

[0057] The first aspect of the present application provides a negative electrode plate, Figure 1 Schematic diagram of the structure of the negative electrode sheet of one embodiment of the present application. Figure 1 As shown, the negative electrode plate 121 includes a negative electrode current collector 122 and a negative electrode film layer 123 provided on at least one side of the negative electrode current collector 122; the negative electrode film layer 123 includes a negative electrode active material and a binder, and the negative electrode active material includes a silicon-based material; wherein the binder includes at least one of the following functional groups: hydroxyl, carboxyl, amino, cyano, lipid, and vinyl.

[0058] Adding silicon-based materials and binders to the negative electrode film layer 123, and making the binder include at least one functional group of hydroxyl, carboxyl, amino, cyano, lipid, and vinyl, can improve the adhesion and cohesion of the negative electrode sheet to inhibit the expansion of the negative electrode sheet, thereby improving the cycle performance of the battery.

[0059] In the embodiments of the present application, silicon-based materials refer to materials grown through different process steps using silicon materials as substrates or bases, including silicon materials on insulating layers, germanium silicon materials, porous silicon, microcrystalline silicon, and other compound semiconductor materials grown heteroepitaxially using silicon as a substrate.

[0060] In an embodiment of the present application, an acrylate compound can be introduced into the adhesive so that the adhesive includes a lipid base; that is, the adhesive can include an acrylate compound, wherein the acrylate compound includes at least one of methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, tert-butyl acrylate, methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, and tert-butyl methacrylate.

[0061] In the embodiment of the present application, a multifunctional vinyl compound can be introduced into the binder so that the binder includes vinyl groups. That is, the binder can include a multifunctional vinyl compound, the multifunctional vinyl compound includes two or more vinyl groups, and the multifunctional vinyl compound includes at least one of divinylbenzene, diethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, and diallyl phthalate.

[0062] Generally, a battery cell includes a positive electrode, a separator, a negative electrode, and an electrolyte. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive and negative electrodes. The electrolyte plays the role of transferring ions between the positive and negative electrodes. The separator is set between the positive and negative electrodes, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0063] It should be noted here that the “positive electrode sheet” and “negative electrode sheet” mentioned in the embodiments of the present application refer to the positive electrode sheet and the negative electrode sheet as a whole including active materials, current collectors or other additives.

[0064] The negative electrode sheet 121 includes a negative electrode current collector 122 and a negative electrode film layer 123 disposed on at least one surface of the negative electrode current collector 122 , wherein the negative electrode film layer 123 includes a negative electrode active material.

[0065] As an example, the negative electrode current collector 122 has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer 123 is disposed on any one or both of the two opposite surfaces of the negative electrode current collector 122 .

[0066] In the above solution, the negative electrode sheet 121 includes a negative electrode film layer 123, further, the negative electrode film layer 123 includes a negative electrode active material and a binder, and further, the negative electrode active material includes a silicon-based material, wherein the volume average particle size Dv50 of the binder is 0.3 μm-0.7 μm. By adding silicon-based materials and binders to the negative electrode film layer 123, on the one hand, the theoretical specific capacity of the silicon-based material is higher, which is beneficial to improving the energy density of the battery; on the other hand, the silicon-based material is harder and not easily crushed when cold pressed, and the particle shape is relatively irregular, with certain gaps between particles. Therefore, the negative electrode sheet 121 containing silicon-based materials generally has a larger porosity, and the binder containing at least one of hydroxyl, carboxyl, amino, cyano, lipid, and vinyl has better adhesion. Adding a binder with better adhesion to the negative electrode film layer 123 so that the binder is filled in the large pores of the silicon-based material can improve the cohesive force of the negative electrode sheet 121 and the adhesion between the negative electrode film layer 123 and the negative electrode collector 122, so as to inhibit the serious volume expansion of the silicon-based material during the battery cycle and reduce the demolding and powder loss of the negative electrode sheet, thereby improving the cycle performance of the battery.

[0067] It should be noted here that “demolding” of the electrode sheet refers to partial or complete detachment of the negative electrode film layer 123 from the negative electrode current collector 122 ; and “powder loss” of the electrode sheet refers to the detachment of the negative electrode active material from the negative electrode current collector 122 .

[0068] In some embodiments, the volume average particle size Dv50 of the binder is 0.1 μm-0.8 μm; optionally, the volume average particle size distribution Dv50 of the binder is 0.3 μm-0.7 μm; optionally, the volume average particle size Dv50 of the binder is 0.35 μm-0.45 μm.

[0069] In the above scheme, in order to improve the bonding force of the negative electrode plate 121 and improve the demoulding and powdering of the plate, a binder having at least one functional group of hydroxyl, carboxyl, amino, cyano, lipid, and vinyl is added to the negative electrode film layer to fill in the larger gaps of the silicon-based material. In addition, by making the volume average particle size Dv50 of the binder 0.1μm-0.8μm, further, 0.3μm-0.7μm, and further, 0.35μm-0.45μm, the binder with a moderate particle size can be filled in the larger gaps of the silicon-based material, enhancing the bonding force between the negative electrode active materials and between the negative electrode active materials and the negative electrode current collector 122, thereby further reducing the demoulding and powdering of the plate, and improving the cycle stability of the battery.

[0070] It should be noted here that the volume average particle size Dv50 of the binder may be 0.1 μm, 0.3 μm, 0.5 μm, 0.6 μm, or any value within the range consisting of the above values.

[0071] In some embodiments, the volume average particle size Dv50 of the binder is 0.5 μm to 0.7 μm.

[0072] In the above scheme, in order to improve the bonding force of the negative electrode sheet 121 and improve the demoulding and powdering of the sheet, a binder including at least one functional group of hydroxyl, carboxyl, amino, cyano, lipid, and vinyl is added to the negative electrode film layer 123 to fill the larger gaps in the silicon-based material. Furthermore, by making the volume average particle size Dv50 of the binder 0.5μm-0.7μm, the bonding force in the negative electrode sheet 121 can also be enhanced, the demoulding and powdering of the negative electrode sheet 121 can be reduced, and the cycle stability of the battery can be improved.

[0073] In some embodiments, the degree of crosslinking of the binder is 50-100, and optionally, the degree of crosslinking of the binder is 80-98.

[0074] The degree of crosslinking is an indicator of the polymerization reaction, and the degree of crosslinking has a relatively important influence on the binder. When the degree of crosslinking is higher, the cohesive force of the binder is stronger, the amount of liquid it absorbs, such as the amount of electrolyte in the battery, will be less, the film formation will be slower, and the strength of the binder will be higher. However, when the degree of crosslinking of the binder is too high, its internal cohesive force is too strong, which will lead to poor rheological properties of the binder, which will have an adverse effect on the fast charging performance of the battery.

[0075] In the above scheme, by maintaining the cross-linking degree of the binder at 50-100, especially 80-98, the strength of the binder and the electrolyte resistance performance can be improved. Maintaining the high strength of the binder is beneficial to inhibiting the expansion of the negative electrode and improving the bonding force between the active materials in the negative electrode plate 121, so as to reduce the probability of powder loss and demolding of the negative electrode plate 121.

[0076] It should be noted here that the degree of crosslinking of the binder can be 50, 60, 80, 90, or any value within the range of the above values.

[0077] In some embodiments, the swelling ratio of the binder is 5%-80%. Optionally, the swelling ratio of the binder is 10%-50%.

[0078] Swelling refers to the phenomenon that the volume of the binder changes in the liquid. The swelling rate refers to the degree to which the binder expands when it absorbs the liquid.

[0079] Binders usually swell, but if the swelling exceeds a certain degree, it will affect the strength and bonding properties of the binder, affect the bonding force between the active material and the current collector in the battery, and further affect various aspects of the battery performance.

[0080] In the above scheme, by limiting the swelling rate of the binder to 5%-50%, especially 10%-30%, the binder with a moderate swelling rate can achieve a better bonding effect and have a higher strength, thereby effectively inhibiting the expansion of the negative electrode sheet 121 and further reducing the probability of powder loss and demolding of the negative electrode sheet 121.

[0081] It should be noted here that the swelling ratio of the binder can be 5%, 10%, 20%, 40% or any value within the range of the above values.

[0082] In some embodiments, the glass transition temperature of the binder is -20°C to 60°C. Alternatively, the glass transition temperature of the binder is -10°C to 40°C.

[0083] The glass transition temperature refers to the temperature corresponding to the transition from the glass state to the highly elastic state. If the glass transition temperature is too high, the negative electrode plate 121 will become brittle, which will further cause the negative electrode plate 121 to release from the mold and fall off during the battery cycle.

[0084] In the above solution, the brittleness of the negative electrode sheet 121 can be further reduced by maintaining the glass transition temperature of the binder at -20°C-60°C, especially -10°C-40°C.

[0085] It should be noted here that the glass transition temperature of the binder may be -10°C, 10°C, 25°C, 40°C, or any value within the range consisting of the above values.

[0086] In some embodiments, the elongation of the adhesive is 50%-400%. Optionally, the elongation of the adhesive is 100%-200%.

[0087] Elongation refers to the percentage of the elongation of the original gauge length after the material breaks under tension to the original gauge length.

[0088] Regarding the binder, during the repeated expansion of the negative electrode sheet 121 , a binder with a certain elongation can suppress the expansion of the negative electrode sheet 121 , thereby reducing the rupture or powdering of the negative electrode sheet 121 .

[0089] In the above scheme, by making the elongation of the adhesive be 50%-400%, especially 100%-200%, the adhesive can have a stronger anti-deformation performance.

[0090] It should be noted here that the elongation of the adhesive may be 50%, 100%, 200%, 350%, or any value within the range consisting of the above values.

[0091] In some embodiments, based on 100 parts by weight of the negative electrode film layer 123 , the weight of the binder is 1 part by weight to 10 parts by weight. Optionally, the weight of the binder is 2 parts by weight to 8 parts by weight.

[0092] In the above scheme, in order to reduce the demoulding and powdering of the negative electrode sheet 121, a binder with a larger volume average particle size is added to the negative electrode film layer 123, so that the binder fills the larger pores in the negative electrode active material. By making the mass proportion of the binder in the negative electrode film layer 123 1%-10%, especially 2%-8%, it can not only improve the bonding force between the negative electrode active materials to inhibit the volume expansion of the negative electrode sheet 121, but also reduce the reduction in battery energy density caused by excessive binder content.

[0093] It should be noted here that, based on 100 parts by weight of the negative electrode film layer 123 , the weight of the binder can be 1 part by weight, 5 parts by weight, 6 parts by weight, 8 parts by weight, and any value within the range of the above values.

[0094] In a possible implementation, the binder includes at least one of styrene-butadiene and its modifications, styrene-acrylic and its modifications, polyurethane and its modifications, polyvinylidene fluoride and its modifications, and acrylate and its modifications.

[0095] In the embodiment of the present application, by using at least one of butadiene styrene and its modified products, styrene acrylic and its modified products, polyurethane and its modified products, polyvinylidene fluoride and its modified products, acrylate and its modified products with good bonding strength as a binder, it helps to further improve the bonding strength between the negative electrode active material and the negative electrode current collector 122.

[0096] In a possible implementation, the silicon-based material includes at least one of a silicon-oxygen material and a silicon-carbon material; optionally, the silicon-oxygen material includes SiO x , wherein 0.4≤x≤1.6; optionally, the silicon-carbon material includes a silicon-carbon composite, and based on the total mass of the silicon-carbon composite, the ratio of the mass content B of the carbon element to the mass content A of the silicon element in the silicon-carbon composite is 1.3≤B / A≤2.

[0097] It should be noted here that silicon-oxygen material refers to a compound composed of silicon and oxygen; silicon-carbon material refers to a compound composed of silicon and carbon.

[0098] In the above scheme, by adding silicon-based materials, especially silicon-oxygen materials or silicon-carbon materials, to the negative electrode active materials, it is beneficial to improve the energy density of the battery. The silicon-oxygen materials in the silicon-based materials not only have high theoretical capacity and excellent stability, but also have the advantages of low cost, non-toxicity and environmental friendliness; silicon-carbon materials have high theoretical capacity and good cycle performance. By using silicon-oxygen materials, especially SiOx , wherein 0.4≤x≤1.6, or using a silicon-carbon material in which the ratio of the mass proportion of silicon element to the silicon-carbon composite A to the mass proportion of carbon element to the silicon-carbon composite B is 1.3≤B / A≤2, can further improve battery performance.

[0099] It should be noted here that, in the silicon-carbon material, the mass ratio B / A of carbon element to silicon element can be 1.3, 1.5, 1.7, 3 and any value within the range of the above values.

[0100] In some embodiments, the negative electrode active material further comprises graphite; wherein, based on 100 parts by weight of the negative electrode film layer 123 , the weight of the graphite is 45 parts by weight to 70 parts by weight, and optionally, the weight of the graphite is 55 parts by weight to 65 parts by weight.

[0101] In the above scheme, silicon-based materials have a high theoretical capacity, but their conductivity is poor. Therefore, if only silicon-based materials are used as the negative electrode active material of the battery, the conductivity of the battery will be very poor. By adding graphite with good conductivity to the negative electrode active material and making the mass proportion of graphite in the negative electrode film layer 123 45%-70%, especially 55%-65%, the battery can maintain good cycle performance.

[0102] It should be noted here that, based on 100 parts by weight of the negative electrode film layer 123 , the weight of graphite can be 50 parts by weight, 58 parts by weight, 65 parts by weight, 72 parts by weight, and any value within the range of the above values.

[0103] In some embodiments, the compaction density of the negative electrode sheet 121 is 1.0 g / cm 3 -2.5g / cm 3 Optionally, the compaction density of the negative electrode sheet 121 is 1.2 g / cm 3 -1.8g / cm 3 .

[0104] In the above scheme, by making the compaction density of the negative electrode sheet 121 to be 1.0 g / cm 3 -2.5g / cm 3 , especially 1.2g / cm 3 -1.8g / cm 3 , which can further improve the energy density of the battery.

[0105] It should be noted that the compaction density of the negative electrode sheet 121 can be 1g / cm 3 , 1.5g / cm 3 , 2.2g / cm 3 , 2.5g / cm 3and any value within the range consisting of the above values.

[0106] In some embodiments, the thickness d1 of the negative electrode sheet 121 is 60 μm-150 μm. Optionally, the thickness d1 of the negative electrode sheet 121 is 90 μm-130 μm.

[0107] In the above solution, by making the thickness d1 of the negative electrode sheet 121 be 60 μm-150 μm, especially 90 μm-130 μm, the energy density of the battery can be further improved.

[0108] It should be noted here that the thickness d1 of the negative electrode sheet 121 can be 60 μm, 80 μm, 100 μm, 120 μm, or any value within the range of the above values.

[0109] In some embodiments, the negative electrode current collector 122 may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0110] In some embodiments, the negative electrode active material may also include negative electrode active materials for batteries known in the art. As an example, in addition to silicon-based materials, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, tin-based materials, lithium titanate, etc. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. In addition, the silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0111] In some embodiments, the binder may be selected from at least one of styrene-butadiene rubber (SBR), polyurethane (PU), nitrile rubber (NBR), polyvinylidene fluoride (PVDF), and styrene acrylic emulsion (SAR).

[0112] In some embodiments, the negative electrode film layer 123 may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0113] In some embodiments, the negative electrode film layer 123 may further include other auxiliary agents, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0114] In some embodiments, the negative electrode sheet 121 can be prepared in the following manner: the components for preparing the negative electrode sheet 121, such as the negative electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector 122, and after drying, cold pressing and other processes, the negative electrode sheet 121 can be obtained.

[0115] [Positive electrode]

[0116] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes a positive electrode active material.

[0117] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0118] In some embodiments, the positive electrode active material includes Li x (Ni a Co b Mn c ) 1-d M d O 2-y A y , wherein M includes at least one of Zr, Al, B, Ta, Mo, W, Nb, Sb, and La, 0.2<x≤1.2, 0.5≤a<1.0, 0≤b<0.5, 0≤c<1, 0≤d<1, and 0≤y<0.02.

[0119] It should be noted here that the positive electrode active materials include but are not limited to the following substances: Li 0.5 Ni 0.5 Co 0.1 Mn 0.4 O2、Li 0.5 (Ni 0.5 Co 0.1 Mn 0.4 ) 0.5 Zr 0.5 O 1.9 A 0.1 、LiNi 0.4 Co 0.3 Mn 0.3 O2.

[0120] It should be noted that in the positive electrode sheet, battery or electrical device, lithium ions will be consumed as the battery goes through the formation and circulation processes, so the lithium content in the positive electrode active material measured will be less than 1. At the same time, if the positive electrode sheet is supplemented with lithium, the lithium content in the positive electrode active material measured will be greater than 1 after the battery goes through the formation and circulation processes.

[0121] Similarly, in the list of positive electrode materials in this application, the molar content of O is only a theoretical value. The release of oxygen from the lattice will cause the molar content of oxygen to change, and the actual molar content of O will fluctuate.

[0122] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0123] In some embodiments, the positive electrode active material may also adopt positive electrode active materials for batteries that are well known in the art. As an example, the positive electrode active material may include at least one of the following materials: lithium-containing phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM523), LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM211), LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM622), LiNi0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM811), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0124] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0125] In some embodiments, the positive electrode film layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0126] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry, and the positive electrode slurry is coated on the positive electrode collector. After drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0127] [Electrolytes]

[0128] The electrolyte plays a role in conducting ions between the positive electrode plate and the negative electrode plate 121. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.

[0129] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0130] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0131] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0132] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0133] [Isolation film]

[0134] In some embodiments, the battery cell further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0135] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0136] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0137] In some embodiments, the battery cell may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.

[0138] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0139] The present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square or any other shape. Figure 2 It is a schematic diagram of a battery cell according to an embodiment of the present application.

[0140] Figure 3 Schematic diagram of the structure of a battery cell according to an embodiment of the present application. Figure 3As shown, the outer packaging of the battery cell 100 includes a shell 11 and a cover plate 13. Among them, the shell 11 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate are enclosed to form a receiving cavity. The shell 11 has an opening connected to the receiving cavity, and the cover plate 13 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet 121 and the isolation film can form an electrode assembly 12 through a winding process or a lamination process. The electrode assembly 12 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 12. The number of electrode assemblies 12 contained in the battery cell 100 can be one or more, and those skilled in the art can select according to specific actual needs.

[0141] In some embodiments, the battery cells 100 may also be assembled into a battery module. The battery module may contain one or more battery cells 100. The specific number may be selected by those skilled in the art according to the application and capacity of the battery module.

[0142] Figure 4 is a schematic diagram of a battery according to one embodiment of the present application, Figure 5 Schematic diagram of the structure of a battery according to one embodiment of the present application. Figure 4 and Figure 5 The battery 400 may include a battery box and a plurality of battery cells 100 disposed in the battery box. The battery box includes an upper box body 401 and a lower box body 402. The upper box body 401 can cover the lower box body 402 and form a closed space for accommodating the battery cells 100. The plurality of battery cells 100 may be arranged in the battery box in any manner.

[0143] In addition, the present application also provides an electric device, which includes at least one of the negative electrode plate 121, battery cell 100 or battery 400 provided in the present application. The negative electrode plate 121, battery cell 100 or battery 400 can be used as a power source for the electric device, and can also be used as an energy storage unit for the electric device. The electric device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0144] For example, Figure 6 Schematic diagram of the structure of an electric device according to an embodiment of the present application. Figure 6As shown, the electrical device is a vehicle 1, and the vehicle 1 may be a fuel vehicle, a gas vehicle or a new energy vehicle, and the new energy vehicle may be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. A motor 500, a controller 600 and a battery 400 may be arranged inside the vehicle 1, and the controller 600 is used to control the battery 400 to supply power to the motor 500. For example, a battery 400 may be arranged at the bottom, front or rear of the vehicle 1. The battery 400 may be used to power the vehicle 1, for example, the battery 400 may be used as an operating power source for the vehicle 1, for the circuit system of the vehicle 1, for example, for the working power requirements during the start-up, navigation and operation of the vehicle 1. In another embodiment of the present application, the battery 400 may not only be used as an operating power source for the vehicle 1, but also as a driving power source for the vehicle 1, replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 1.

[0145] As the electrical device, the negative electrode sheet 121, the battery cell 100 or the battery 400 can be selected according to its usage requirements.

[0146] The electric device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the electric device's requirements for high power and high energy density of the battery, a battery cell 100 or a battery 400 may be used.

[0147] As another example, the device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be light and thin, and the battery cell 100 may be used as a power source.

[0148] [Example]

[0149] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0150] [Example 1]

[0151] 1.) Preparation of lithium-ion batteries

[0152] 1.1) Preparation of negative electrode sheet:

[0153] 1.11). Preparation of silicon-carbon material: comprising providing a gas containing a silicon precursor to carbon matrix particles having a carbon skeleton, and generating silicon nanoparticles attached to the carbon skeleton from the silicon precursor through chemical vapor deposition to obtain a carbon-silicon composite material (hereinafter referred to as silicon-carbon material).

[0154] 1.12) Preparation of binder: Mix a part of emulsifier, a part of acrylate monomer, a part of styrene monomer and water to prepare pre-emulsion; Mix another part of emulsifier, another part of acrylate monomer, another part of styrene monomer and water, then add initiator to initiate polymerization to prepare seed emulsion; Add the pre-emulsion to the seed emulsion in a dropwise manner, add initiator to carry out polymerization reaction, and obtain styrene-acrylic emulsion with a latex ball Dv50 particle size of 100nm-900nm; wherein the total mass of the emulsifier is 0.7% to 5% of the total mass of the prepared monomers, and can be optionally 1% to 4.5%; the prepared monomers include acrylate monomers and styrene monomers. Based on the total mass of the prepared monomers, the styrene-acrylic emulsion includes 30%-80% styrene monomers, 20%-70% acrylate monomers and 0-10% functional monomers in terms of mass percentage; the functional monomer methacrylic acid is added in the step of preparing the pre-emulsion and / or seed emulsion.

[0155] 1.13) Preparation of negative electrode sheet: The first active material artificial graphite and the second active material silicon carbon material, the conductive agent acetylene black, the conductive agent single-wall CNT, the binder styrene acrylic emulsion, and the thickener CMC-Na are mixed in a proper amount of deionized water solvent system at a weight ratio of 64.4%:30%:1%:0.1%:3.5%:1% to obtain the negative electrode active material, and the negative electrode active material is coated on the Cu foil, and then dried, cold pressed, and cut to obtain the negative electrode sheet, wherein the binder styrene acrylic emulsion contains a functional group carboxyl, the weight of the binder is 3.5 parts by weight, the volume average particle size Dv50 is 0.45μm, the degree of crosslinking is 80, the swelling rate is 25%, the glass transition temperature is 20°C, and the elongation is 100%.

[0156] 1.2) Preparation of positive electrode sheet: The positive electrode active material lithium nickel cobalt manganese oxide (LiNi 0.6 Co 0.2 Mn 0.2 O2), conductive agent carbon nanotubes (CNT), and binder polyvinylidene fluoride (PVDF) are dissolved in a solvent N-methylpyrrolidone (NMP) in a weight ratio of 96%:2%:2%, and the positive electrode active material is prepared after being fully stirred and mixed. The positive electrode active material is coated on Al foil, and then dried, cold pressed, and cut to obtain a positive electrode sheet.

[0157] 1.3). Preparation of diaphragm: PE porous polymer film is used as the isolation membrane.

[0158] 1.4). Electrolyte: Dissolve EC / EMC / DMC in 1M LiPF6 at a volume ratio of 1:1:1 and stir evenly.

[0159] 1.5) Assembly: stack the positive electrode sheet, separator, and negative electrode sheet in order, so that the separator is in the middle of the positive and negative electrodes to play a role of isolation, and wind them to get the electrode assembly, and add electrolyte. Then hot press at 100℃ and 250MPa for 2min to get the lithium-ion battery.

[0160] [Example 2]

[0161] The preparation method of the lithium-ion battery of Example 2 is substantially the same as that of Example 1, except that the volume average particle size Dv50 of the binder in the negative electrode plate in Example 2 is 0.3 μm.

[0162] [Example 3]

[0163] The preparation method of the lithium-ion battery of Example 3 is substantially the same as that of Example 1, except that the volume average particle size Dv50 of the binder in the negative electrode plate in Example 3 is 0.35 μm.

[0164] [Example 4]

[0165] The preparation method of the lithium-ion battery of Example 4 is substantially the same as that of Example 1, except that the volume average particle size Dv50 of the binder in the negative electrode plate in Example 4 is 0.5 μm.

[0166] [Example 5]

[0167] The preparation method of the lithium-ion battery of Example 5 is substantially the same as that of Example 1, except that the volume average particle size Dv50 of the binder in the negative electrode plate in Example 5 is 0.7 μm.

[0168] [Example 6]

[0169] The preparation method of the lithium ion battery of Example 6 is substantially the same as that of Example 1, except that the degree of crosslinking of the binder in the negative electrode plate of Example 6 is 50.

[0170] [Example 7]

[0171] The preparation method of the lithium ion battery of Example 7 is substantially the same as that of Example 1, except that the degree of crosslinking of the binder in the negative electrode plate of Example 7 is 85.

[0172] [Example 8]

[0173] The preparation method of the lithium ion battery of Example 8 is basically the same as that of Example 1, except that the degree of crosslinking of the binder in the negative electrode plate in Example 8 is 98.

[0174] [Example 9]

[0175] The preparation method of the lithium ion battery of Example 9 is substantially the same as that of Example 1, except that the degree of crosslinking of the binder in the negative electrode plate of Example 9 is 100.

[0176] [Example 10]

[0177] The preparation method of the lithium ion battery of Example 10 is substantially the same as that of Example 1, except that the swelling rate of the binder in the negative electrode plate in Example 10 is 5%.

[0178] [Example 11]

[0179] The preparation method of the lithium ion battery of Example 11 is substantially the same as that of Example 1, except that the swelling rate of the binder in the negative electrode plate in Example 11 is 10%.

[0180] [Example 12]

[0181] The preparation method of the lithium ion battery of Example 12 is basically the same as that of Example 1, except that the swelling rate of the binder in the negative electrode plate in Example 12 is 50%.

[0182] [Example 13]

[0183] The preparation method of the lithium ion battery of Example 13 is substantially the same as that of Example 1, except that the swelling rate of the binder in the negative electrode plate in Example 13 is 80%.

[0184] [Example 14]

[0185] The preparation method of the lithium-ion battery of Example 14 is basically the same as that of Example 1, except that the glass transition temperature of the binder in the negative electrode plate in Example 14 is -20°C.

[0186] [Example 15]

[0187] The preparation method of the lithium-ion battery of Example 15 is basically the same as that of Example 1, except that the elongation of the binder in the negative electrode plate in Example 15 is 60°C.

[0188] [Example 16]

[0189] The preparation method of the lithium-ion battery of Example 16 is basically the same as that of Example 1, except that the glass transition temperature of the binder in the negative electrode plate in Example 16 is 200%.

[0190] [Example 17]

[0191] The preparation method of the lithium-ion battery of Example 17 is basically the same as that of Example 1, except that the glass transition temperature of the binder in the negative electrode plate in Example 17 is 50%.

[0192] [Example 18]

[0193] The preparation method of the lithium-ion battery of Example 18 is basically the same as that of Example 1, except that the glass transition temperature of the binder in the negative electrode plate in Example 18 is 400%.

[0194] [Example 19]

[0195] The preparation method of the lithium-ion battery of Example 19 is basically the same as that of Example 1, except that the weight portion of the binder in the negative electrode plate in Example 19 is 1 weight portion, that is, the mass ratio of the first active material artificial graphite and the second active material silicon-carbon material, the conductive agent acetylene black, the conductive agent single-wall CNT, the binder styrene acrylic emulsion (SAR), and the thickener CMC-Na is 66.9%:30%:1%:0.1%:1%:1%.

[0196] [Example 20]

[0197] The preparation method of the lithium-ion battery of Example 20 is basically the same as that of Example 1, except that the weight ratio of the binder in the negative electrode plate in Example 20 is 2 parts by weight, that is, the mass ratio of the first active material artificial graphite and the second active material silicon-carbon material, the conductive agent acetylene black, the conductive agent single-wall CNT, the binder styrene acrylic emulsion (SAR), and the thickener CMC-Na is 65.9%:30%:1%:0.1%:2%:1%.

[0198] [Example 21]

[0199] The preparation method of the lithium-ion battery of Example 21 is basically the same as that of Example 1, except that the weight ratio of the binder in the negative electrode plate in Example 21 is 6 parts by weight, that is, the mass ratio of the first active material artificial graphite and the second active material silicon-carbon material, the conductive agent acetylene black, the conductive agent single-wall CNT, the binder styrene acrylic emulsion (SAR), and the thickener CMC-Na is 61.9%:30%:1%:0.1%:6%:1%.

[0200] [Example 22]

[0201] The preparation method of the lithium-ion battery of Example 22 is basically the same as that of Example 1, except that the weight proportion of the binder in the negative electrode plate in Example 22 is 8 weight proportions, that is, the mass ratio of the first active material artificial graphite and the second active material silicon-carbon material, the conductive agent acetylene black, the conductive agent single-wall CNT, the binder styrene acrylic emulsion (SAR), and the thickener CMC-Na is 59.9%:30%:1%:0.1%:8%:1%.

[0202] [Example 23]

[0203] The preparation method of the lithium-ion battery of Example 23 is basically the same as that of Example 1, except that the binder in the negative electrode plate in Example 23 is a polyurethane emulsion.

[0204] [Example 24]

[0205] The preparation method of the lithium-ion battery of Example 24 is basically the same as that of Example 1, except that the binder in the negative electrode plate in Example 24 is nitrile rubber emulsion.

[0206] [Example 25]

[0207] The preparation method of the lithium-ion battery of Example 25 is basically the same as that of Example 1, except that the binder in the negative electrode plate in Example 25 contains hydroxyl groups.

[0208] [Example 26]

[0209] The preparation method of the lithium-ion battery of Example 26 is basically the same as that of Example 1, except that the binder in the negative electrode plate in Example 26 contains amino groups.

[0210] [Example 27]

[0211] The preparation method of the lithium-ion battery of Example 27 is basically the same as that of Example 1, except that the binder in the negative electrode plate in Example 27 contains cyano group.

[0212] [Example 28]

[0213] The preparation method of the lithium-ion battery of Example 28 is basically the same as that of Example 1, except that the volume average particle size Dv50 of the binder in the negative electrode plate in Example 28 is 1 μm.

[0214] [Example 29]

[0215] The preparation method of the lithium-ion battery of Example 29 is basically the same as that of Example 1, except that the volume average particle size Dv50 of the binder in the negative electrode plate in Example 29 is 0.1 μm.

[0216] [Example 30]

[0217] The preparation method of the lithium-ion battery of Example 30 is basically the same as that of Example 1, except that the volume average particle size Dv50 of the binder in the negative electrode plate in Example 30 is 0.8 μm.

[0218] [Comparative Example 1]

[0219] The preparation method of the lithium ion battery of Comparative Example 1 is substantially the same as that of Example 1, except that no functional group is introduced into the binder in the negative electrode sheet of Comparative Example 1.

[0220] [Comparative Example 2]

[0221] The preparation method of the lithium ion battery of Comparative Example 2 is substantially the same as that of Example 1, except that the binder in the negative electrode sheet of Comparative Example 2 contains hydroxyl groups.

[0222] [Comparative Example 3]

[0223] The preparation method of the lithium ion battery of Comparative Example 3 is substantially the same as that of Example 1, except that the volume average particle size Dv50 of the binder in the negative electrode plate of Comparative Example 3 is 1 μm.

[0224] [Comparative Example 4]

[0225] The preparation method of the lithium-ion battery of Comparative Example 4 is substantially the same as that of Example 1, except that the volume average particle size Dv50 of the binder in the negative electrode sheet in Comparative Example 4 is 5 μm.

[0226] [Comparative Example 5]

[0227] The preparation method of the lithium-ion battery of Comparative Example 5 is substantially the same as that of Example 1, except that the volume average particle size Dv50 of the binder in the negative electrode plate in Comparative Example 5 is 0.2 μm.

[0228] 2). Performance characterization of negative electrode sheets of lithium-ion batteries

[0229] 2.1) Measurement of volume average particle size Dv50: It can be tested with a laser particle size analyzer (such as Master Size 3000) according to GB / T 19077-2016 particle size distribution laser diffraction method.

[0230] 2.2) Measurement of cross-linking degree: It can be tested according to GB / T 36965-2018 or IEC 60811-507-2012.

[0231] 2.3) Measurement of swelling rate: Take 20g sample into a polytetrafluoroethylene culture dish, and then place it in a 100℃ oven to dry to constant weight; cut the dry film into 20×80mm, and weigh the weight of the sample W0; put the dry film into a plastic bottle containing electrolyte, keep it at a constant temperature of 60℃, and measure the mass W1, W2, W3, W4, W5, and W6 at intervals of 12h, 24h, 36h, 48h, 60h, and 72h respectively; calculate the swelling rate at different time lengths using the following formula: (Wn-W0) / W0×100%.

[0232] 2.4) Measurement of glass transition temperature: According to the standard ISO 11357-2:1999, the glass transition temperature can be measured using a differential scanning calorimeter.

[0233] 2.5) Measurement of elongation

[0234] 2.51). Film preparation:

[0235] 1. Pretreatment: Pour the sample into a 1L water cup and seal it with plastic wrap and let it stand for more than 24 hours to eliminate bubbles; 2. Scraping method: Pour the adhesive into a 280mm×160mm×3mm acrylic slot for scraping and let it stand at room temperature for 30 minutes (to remove bubbles); 3. Oven drying: Place it in a vacuum drying at 60℃ (a level gauge is required to calibrate the tray in the oven), and it will form a film after baking for 12 hours; 4. Demolding treatment: After the film is formed, place the slot in an environment with a humidity of ≤60% for more than 12 hours to dilute it, and then the film can be removed;

[0236] 2.52). Film stretching:

[0237] 1. Film sample preparation: Cut the film into strips of 150mm×20mm;

[0238] 2. Sample selection: select the film strips with uniform thickness (cov < 3.0%) and no bubbles within 50 mm in the longitudinal direction;

[0239] 3. Tensile test: Use a tensile testing device to stretch the prepared film at a speed of 10 mm / min until it breaks; calculate the elongation from the stretching displacement;

[0240] 2.6) Measurement of compaction density: For details, refer to GB / T 24533-2009. Take a certain amount of powder and put it in a special compaction mold, then put the mold on the compaction density instrument, weigh the weight m of the powder, and set the pressure to 400kN. The thickness (thickness after unloading) and volume v of the powder can be read on the equipment, and the compaction density can be calculated by ρ=m / v.

[0241] 2.7) Detection of functional groups: It can be characterized by infrared, please refer to GB / T 6040-2019 for details.

[0242] Table 1 Specific binder parameters of Examples 1-30 and Comparative Examples 1-5

[0243]

[0244]

[0245] 3). Lithium-ion battery performance characterization

[0246] 3.1) Cycle performance test: At 45°C, keep the battery charge and discharge voltage range at 2.5-4.35V, cycle at 1C current density, and record the battery capacity retention rate after 200 cycles. The test results are shown in Table 2.

[0247] 3.2) Test of the bonding strength of the negative electrode sheet: Measure the negative electrode sheet to be tested in the direction perpendicular to the mechanical direction (TD), cut a sample with a width of 20mm and a length of 100-160mm, and stick the special double-sided tape on the steel plate. The tape width is 20mm and the length is 90-150mm. After sticking the cut electrode sheet sample on the double-sided tape, use a 2Kg hand roller to roll it three times in the same direction, and use a tensile machine to test the bonding strength of the electrode sheet. The greater the bonding strength between the negative electrode film layer and the negative electrode current collector in the negative electrode sheet, the stronger the interaction between the active substance and the current collector in the negative electrode film layer. Conversely, it indicates that the interaction between the active substance and the current collector in the negative electrode film layer is worse.

[0248] 3.3) Test of the cohesive force of the negative electrode sheet: Cut a negative electrode sheet sample with a width of 20mm and a length of 100mm. Paste the cut electrode sheet sample on the double-sided tape, and then paste the green tape on the electrode sheet sample. The width of the green tape is 20mm and the length is 120mm. The green glue of the non-contact electrode sheet is pasted on a paper sheet with a width of 20mm and a length of 60mm. The paper sheet and the green glue are in a straight line. The joint part of the green glue and the paper sheet is bonded with wrinkled glue. Before the test, the green glue of the contact electrode sheet needs to be evenly compacted with the double-sided tape, and the cohesive force of the electrode sheet is tested with a tensile machine. The greater the force between the active particles in the negative electrode film layer, the stronger the force between the active substances in the negative electrode sheet. Conversely, it indicates that the force between the active substances in the electrode sheet is worse.

[0249] Table 2 Performance tests of Examples 1-30 and Comparative Examples 1-5

[0250]

[0251]

[0252] In the embodiment of the present application, the bonding force is used to represent the bonding degree between the negative electrode film layer and the negative electrode current collector. The larger the bonding force value is, the stronger the interaction between the negative electrode film layer and the negative electrode current collector is, the better the bonding is, and the lower the probability of demolding of the negative electrode film layer is; the cohesion is used to represent the bonding force between the active materials in the negative electrode film layer. The greater the cohesion is, the tighter the connection between the active materials in the negative electrode film layer is, and the less likely it is to fall off; the 45°C cycle capacity retention rate is used to represent the cycle performance of the battery. The higher the capacity retention rate value is, the better the cycle performance of the battery is.

[0253] According to Examples 1-30 and Comparative Examples 1-5, when the binder includes at least one functional group selected from the group consisting of hydroxyl, carboxyl, amino, acrylamide, and cyano, the negative electrode sheet can have both good bonding and cohesive forces, thereby improving the cycle performance of the battery.

[0254] According to Examples 1-30 and Comparative Examples 3-5, adding a binder having a volume average particle size Dv50 of 0.1 μm-0.8 μm to the negative electrode film layer can make the negative electrode sheet have better bonding force and cohesion, and improve the cycle performance of the battery.

[0255] Further, according to Examples 1-5 and 28-30, adding a binder with a volume average particle size Dv50 of 0.3 μm-0.7 μm, especially a binder with a volume average particle size of 0.35 μm-0.45 μm, to the negative electrode film layer can help further improve the bonding strength, cohesion of the negative electrode sheet and the cycle performance of the battery.

[0256] According to Examples 1, 6-9, by adding a binder to the negative electrode film layer and having a cross-linking degree of not less than 50, the negative electrode plate can have better adhesion and cohesion, thereby reducing demolding and powder loss of the negative electrode plate and providing the battery with better cycle performance; further, maintaining the cross-linking degree of the binder at 80-98 helps to further improve the adhesion and cohesion of the negative electrode plate and the cycle performance of the battery.

[0257] According to Examples 1 and 10-13, by maintaining the swelling rate of the binder added to the negative electrode film layer at 5%-80%, the negative electrode sheet has both good bonding and cohesion, and the cycle performance of the battery is improved; further, by maintaining the swelling rate of the binder at 10%-50%, the bonding and cohesion of the negative electrode sheet and the cycle performance of the battery can be further improved.

[0258] According to Examples 1, 14-15, the glass transition temperature of the binder added to the negative electrode film layer is -20°C-60°C, the negative electrode sheet has good bonding and cohesion, and the cycle performance of the battery is improved.

[0259] According to Examples 1, 16-18, the elongation of the binder added to the negative electrode film layer is 50%-400%, especially 100%-200%, which can improve the bonding force and cohesion of the negative electrode sheet and the cycle performance of the battery.

[0260] According to Examples 1 and 19-22, by making the weight portion of the binder in the negative electrode film layer not less than 1 weight portion, especially 2-8 weight portions, the bonding force and cohesion of the negative electrode sheet, as well as the cycle performance of the battery can be improved.

[0261] It can be seen from Examples 1, 23 and 24 that a variety of adhesives can be applicable to the technical solution of the present application.

[0262] According to Examples 1 and 25-27, various functional groups are applicable to the technical solution of the present application.

[0263] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A negative electrode plate, characterized in that: include: A negative electrode current collector and a negative electrode film layer provided on at least one side of the negative electrode current collector; The negative electrode film layer comprises a negative electrode active material and a binder, wherein the negative electrode active material comprises a silicon-based material; Wherein, the binder includes at least one of the following functional groups: hydroxyl, carboxyl, amino, cyano, lipid, and vinyl.

2. The negative electrode sheet according to claim 1, characterized in that: The volume average particle size Dv50 of the binder is 0.1 μm-0.8 μm; Optionally, the volume average particle size Dv50 of the binder is 0.3 μm-0.7 μm; Optionally, the volume average particle size Dv50 of the binder is 0.35 μm-0.45 μm.

3. The negative electrode sheet according to claim 1, characterized in that: The volume average particle size Dv50 of the binder is 0.5 μm-0.7 μm.

4. The negative electrode sheet according to any one of claims 1 to 3, characterized in that: The crosslinking degree of the binder is 50-100, and optionally, the crosslinking degree of the binder is 80-98.

5. The negative electrode sheet according to any one of claims 1 to 4, characterized in that: The swelling rate of the binder is 5%-80%. Optionally, the swelling rate of the binder is 10%-50%.

6. The negative electrode sheet according to any one of claims 1 to 5, characterized in that: The glass transition temperature of the binder is -20°C-60°C. Optionally, the glass transition temperature of the binder is -10°C-40°C.

7. The negative electrode sheet according to any one of claims 1 to 6, characterized in that: The elongation of the adhesive is 50%-400%. Optionally, the elongation of the adhesive is 100%-200%.

8. The negative electrode sheet according to any one of claims 1 to 7, characterized in that: Based on 100 parts by weight of the negative electrode film layer, the weight of the binder is 1 part by weight to 10 parts by weight. Optionally, the weight of the binder is 2 parts by weight to 8 parts by weight.

9. The negative electrode sheet according to any one of claims 1 to 8, characterized in that: The binder comprises at least one of styrene-butadiene and its modified products, styrene-acrylic and its modified products, polyurethane and its modified products, polyvinylidene fluoride and its modified products, and acrylate and its modified products.

10. The negative electrode sheet according to any one of claims 1 to 9, characterized in that: The silicon-based material includes at least one of a silicon-oxygen material and a silicon-carbon material; Optionally, the silicon-oxygen material includes SiO x , where 0.4≤x≤1.6; Optionally, the silicon-carbon material includes a silicon-carbon composite, and based on the total mass of the silicon-carbon composite, a ratio of a mass content B of carbon element to a mass content A of silicon element in the silicon-carbon composite is 1.3≤B / A≤2.

11. The negative electrode sheet according to any one of claims 1 to 10, characterized in that: The negative electrode active material also includes graphite; Wherein, based on 100 parts by weight of the negative electrode film layer, the weight of the graphite is 45 parts by weight to 70 parts by weight, and optionally, the weight of the graphite is 55 parts by weight to 65 parts by weight.

12. The negative electrode sheet according to any one of claims 1 to 11, characterized in that: The compaction density of the negative electrode plate is 1.0 g / cm 3 -2.5g / cm 3 Optionally, the compaction density of the negative electrode plate is 1.2 g / cm 3 -1.8g / cm 3 .

13. The negative electrode sheet according to any one of claims 1 to 12, characterized in that: The thickness of the negative electrode plate is 60 μm-150 μm. Optionally, the thickness of the negative electrode plate is 90 μm-130 μm.

14. A battery cell, characterized in that: A negative electrode sheet comprising the negative electrode sheet according to any one of claims 1 to 13.

15. The battery cell according to claim 14, characterized in that: The battery cell further comprises a positive electrode sheet, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode film layer disposed on at least one side of the positive electrode current collector, wherein the positive electrode film layer comprises a positive electrode active material.

16. The battery cell according to claim 15, characterized in that: The positive electrode active material includes Li x (Ni a Co b Mn c ) 1-d M d O 2-y A y , wherein M includes at least one of Zr, Al, B, Ta, Mo, W, Nb, Sb, and La, 0.2<x≤1.2, 0.5≤a<1.0, 0≤b<0.5, 0≤c<1, 0≤d<1, and 0≤y<0.

02.

17. A battery, characterized in that: The invention comprises the battery cell according to any one of claims 14 to 16.

18. An electrical device, characterized in that: Comprising the battery of claim 17.

Citation Information

Patent Citations

  • Pole piece, electrochemical device and electronic device

    CN112802990A

  • Pole piece, electrochemical device and electronic device

    CN113646933A

  • Pole piece, electrochemical device and electronic device

    CN113692654A

  • Binder, negative pole piece, electrochemical device and electronic device

    CN116195084A

  • Binder, negative pole piece, battery and electric device

    CN116285882A

Cited By

  • Negative electrode sheet, cell, battery and electric device

    EP4734164A1

  • Secondary battery cell, secondary battery, and electric device

    WO2026144382A1